Temperature dependences and isotherms of galoanomagnetic properties of Bi doped PbTe crystals and thin films - Rogacheva, E.I.; Lyubchenko, S.G.; Vodorez, O.S. (Functional Materials, 2006)
The temperature dependences of galvanomagnetic properties (the Hall coefficient, electrical conductivity, charge carrier mobility) of (PbTe)₁₀₀₋ₓBiₓ (x = 0-1) alloys obtained by doping PbTe with elementary Bi and thin films prepared from these alloys were studied in the temperature range 80-300 K. On the basis of the temperature dependences, the isotherms of the properties were plotted. It was established that a non-monotonic behavior of the dependences of the properties on the Bi concentration, which had been observed earlier at room temperature, is preserved at lower temperatures. This confirms our earlier suggestion about the self-organization processes taking place in the defect subsystem of the crystal at certain Bi concentrations.